2010
DOI: 10.1007/s10333-010-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk assessment for reclaimed wastewater irrigation on paddy rice field in Korea

Abstract: Water shortage has become an important issue for Korean agriculture. Korea suffers from a limited agricultural water supply, and wastewater reuse has been recommended as an alternative solution. This study examined the concentrations of toxic heavy metals and Escherichia coli in a paddy rice field irrigated with reclaimed wastewater to evaluate the risk to farmers. Most epidemiological studies have been based on upland fields, and therefore may not be directly applicable to paddy fields. In this study, a Beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In addition, irrigation with TWW is advantageous to the improvement of soil fertility and rice productivity while reducing the use of commercial fertilizers [3] as a result of the substantial amounts of plant nutrients such as N, P, K, and organic matter available in TWW. However, these benefits are likely countered by substantial concerns about human health risks, owing to potential pathogenic microorganisms, heavy metals, and other contaminants in wastewater [4,5]. Thus, it is necessary to develop new irrigation management strategies and technologies to optimize the advantages while minimizing the aforementioned downsides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, irrigation with TWW is advantageous to the improvement of soil fertility and rice productivity while reducing the use of commercial fertilizers [3] as a result of the substantial amounts of plant nutrients such as N, P, K, and organic matter available in TWW. However, these benefits are likely countered by substantial concerns about human health risks, owing to potential pathogenic microorganisms, heavy metals, and other contaminants in wastewater [4,5]. Thus, it is necessary to develop new irrigation management strategies and technologies to optimize the advantages while minimizing the aforementioned downsides.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with PAHs detected in reclaimed water, Ace, Fl and Ant which existed in reclaimed water were not detected in the 0–600 cm soil profiles. This may be explained by their low concentrations in reclaimed water and easy biodegradability as low‐ring PAHs (Rhee et al, ). In addition, BaA and Chr which were not detected in the reclaimed water were detected in the 0–600 cm soil profiles.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in a province in northern Vietnam [29] assessed the risk of skin disease among farmers occupationally exposed to wastewater, showing that exposure to wastewater is a major risk factor for skin disease, but it is not clear which chemical and biological agents might play the main role in causing the diseases. Rhee et al [30] examined the concentrations of E. coli in a paddy rice field irrigated with reclaimed wastewater and evaluated the risk of its infection among farmers using beta-Poisson doseresponse model. The results showed that the risk was lower in irrigation of groundwater and reclaimed wastewater irrigation than in irrigation of direct effluent from wastewater treatment plant.…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…Irrigated rice cultivation makes up 55% of harvested rice area and contributes to 75% of global rice production [19]. Irrigation of rice paddy using treated or untreated wastewater is extensively practiced and examined in many countries to investigate benefits [20][21][22][23][24][25][26] or drawbacks of the practices [12,[27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%